Transcription factor E4F1 is essential for epidermal stem cell maintenance and skin homeostasis - Lacroix, Matthieu (National Academy of Sciences, 2010)
A growing body of evidence suggests that the multifunctional protein E4F1 is involved in signaling pathways that play essential roles during normal development and tumorigenesis. We generated E4F1 conditional knockout mice to address E4F1 functions in vivo in newborn and adult skin. E4F1 inactivation in the entire skin or in the basal compartment of the epidermis induces skin homeostasis defects, as evidenced by transient hyperplasia in the interfollicular epithelium and alteration of keratinocyte differentiation, followed by loss of cellularity in the epidermis and severe skin ulcerations. E4F1 depletion alters clonogenic activity of epidermal stem cells (ESCs) ex vivo and ends in exhaustion of the ESC pool in vivo, indicating that the lesions observed in the E4F1 mutant skin result, at least in part, from cell-autonomous alterations in ESC maintenance. The clonogenic potential of E4F1 KO ESCs is rescued by Bmi1 overexpression or by Ink4a/Arf or p53 depletion. Skin phenotype of E4F1 KO mice is also delayed in animals with Ink4a/Arf and E4F1 compound gene deficiencies. Our data identify a regulatory axis essential for ESC-dependent skin homeostasis implicating E4F1 and the Bmi1–Arf–p53 pathway.